ENHANCING STUDENTS’ SPEAKING SKILLS THROUGH COMMUNICATIVE LANGUAGE TEACHING: A SYSTEMATIC REVIEW - Nurul Kamaliah; Rahmati (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This study aims to systematically review and synthesize existing research on the effect of Communicative Language Teaching on students’ speaking skills. This study employed a Systematic Literature Review (SLR) following PRISMA guidelines. The reviewed articles were selected from reputable national and international journals published between 2012 and 2025 using predefined inclusion and exclusion criteria. The findings reveal that CLT generally has a positive and significant impact on students’ speaking skills, including fluency, vocabulary development, pronunciation, grammatical accuracy, and interactive competence. However, the review also identifies several methodological limitations, such as small sample sizes, short intervention durations, and the frequent reliance on perception-based instruments rather than performance-based speaking assessments. These findings highlight the need for more rigorous experimental and longitudinal studies to strengthen the empirical evidence of CLT effectiveness and to support evidence-based practices in EFL speaking instruction.